EKSPRESI RELIGIOSITAS PENGHAYAT KEPERCAYAAN TERHADAP TUHAN YANG MAHA ESA DI CILACAP JAWA TENGAH - Zakiyah Zakiyah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
The believers of faith toward God Almighty have been existed since many years ago in Indonesia and there are hundred institutions as groups for those believers. Each of the group has its teaching and ritual as their way of religious expressions. Historically, those groups had experienced of discrimination such as difficulty to get access of civil rights. However, along with the time, they are gradually gained better treatment and the state provides rules that ensure their civil rights. This is a qualitative research and the data of this research were gathered through three methods namely interview, library research and observation. The main focuses of this study are how the teaching and its religious expression of the belivers of faith toward God Almighty. Findings of this study show that there are three elements to look at the religious expressions of the believers of faith toward God Almighty as follows; spirituality, mental and moral ethic. Meanwhile, two of the groups for those believers in Cilacap Central Java namely Suci Hati Kasampurnan (SHK) andPangudi Ilmu Kebatinan Intisarining Rasa (Pikir)have their own religious expression as it is shown on their teaching such as praying to God Almighty and teaching to be a good human being with a good moral and attitude.